Phospholipase D: A new mediator during high phosphate‐induced vascular calcification associated with chronic kidney disease. Issue 4 (12th September 2018) - Skafi, Najwa; Abdallah, Dina; Soulage, Christophe; Reibel, Sophie; Vitale, Nicolas; Hamade, Eva; Faour, Wissam; Magne, David; Badran, Bassam; Hussein, Nader; Buchet, Rene; Brizuela, Leyre; et al.
Abstract: Vascular calcification (VC) is the pathological accumulation of calcium phosphate crystals in one of the layers of blood vessels, leading to loss of elasticity and causing severe calcification in vessels. Medial calcification is mostly seen in patients with chronic kidney disease (CKD) and diabetes. Identification of key enzymes and their actions during calcification will contribute to understand the onset of pathological calcification. Phospholipase D (PLD1, PLD2) is active at the earlier steps of mineralization in osteoblasts and chondrocytes. In this study, we aimed to determine their effects during high‐phosphate treatment in mouse vascular smooth muscle cell line MOVAS, in the ex vivo model of the rat aorta, and in the in vivo model of adenine‐induced CKD. We observed an early increase in PLD1 gene and protein expression along with the increase in the PLD activity in vascular muscle cell line, during calcification induced by ascorbic acid and β‐glycerophosphate. Inhibition of PLD1 by the selective inhibitor VU0155069, or the pan‐PLD inhibitor, halopemide, prevented calcification. The mechanism of PLD activation is likely to be protein kinase C (PKC)‐independent since bisindolylmaleimide X hydrochloride, a pan‐PKC inhibitor, did not affect the PLD activity. In agreement, we found an increase in Pld1 gene expression and PLD activity in aortic explant cultures treated with high phosphate, whereas PLD inhibition by halopemide decreased calcification. Finally, an increase in both Pld1 and Pld2 expression occurred simultaneously with the appearance of VC in a rat model of CKD. Thus, PLD, especially PLD1, promotes VC in the context of CKD and could be an important target for preventing onset or progression of VC. Highlights: PLD1 expression and PLD activity increased in MOVAS cells in a mineralizing medium. PLD1 selective inhibitor, VU0155069, or PLD pan‐inhibitor, halopemide, decreased calcification. Pld1 gene expression and PLD activity increased in mineralized aortic cultures. Pld1 and Pld2 expression increased with the onset of VC in a CKD rat model. Abstract : Phospholipase D (PLD), especially PLD1, promotes vascular calcification (VC) in the context of chronic kidney disease and could be an important target for preventing onset or progression of VC.